The antibacterial activity and toxin production control of bee venom in mouse MRSA pneumonia model - Ryong Kong; Young-Seob Lee; Dam-Hee Kang; Shu Wang; Qianqian Li; Dong-Yeul Kwon; Ok-Hwa Kang (BMC, 2020)
Abstract Background The current antimicrobial therapy is still important for the treatment of pneumonia due to MRSA infection, but there are some limitations, including the route of administration, side effect profile, and increased microbial resistance patterns. Therefore, we investigated whether BV, which shows a strong antimicrobial effect against MRSA, would be effective in a pneumonia model. Methods In vitro, we checked MIC, qRT-PCR, western blot, ELISA, LDH-assay. In vivo, we checked survival rate, gross pathological change, histopathology, lung bacterial clearance assay, and the expression of inflammatory related gene. Results The minimum inhibitory concentration of BV against MRSA is 15.6 μg/ml by broth dilution method. The production of toxins and related gene were reduced by BV in MRSA. The secretion of cytokines were decreased by treatment with BV in 264.7 RAW macrophages stimulated by MRSA Also, BV protected A549 from pathogenicity of MRSA. Bee venom reduced the number of bacteria in the lungs and alleviated the symptoms of MRSA-induced pneumonia in mouse. Conclusion BV inhibited the virulence of the bacterium and the number of bacterial cells present in lung tissue, thereby alleviating the symptoms of pneumonia in mice. This study suggested that BV may be a candidate substance for the treatment of pneumonia caused by MRSA infection.